Plasmodium falciparum infection coinciding with the malaria vaccine candidate BK-SE36 administration interferes with the immune responses in Burkinabe children - Tiono, Alfred B.; Palacpac, Nirianne Marie Q.; Bougouma, Edith Christiane; Nebie, Issa; Ouédraogo, Alphonse; Houard, Sophie; Arisue, Nobuko; D’Alessio, Flavia; Horii, Toshihiro; Sirima, Sodiomon B. (Frontiers in Immunology, 2023)
Background: A vaccine targeting the erythrocyte stages of Plasmodium falciparum could play a role in preventing clinical disease. BK-SE36 is a promising malaria vaccine candidate that has shown a good safety profile and immunological responses during field evaluations. It was observed that repeated natural infections could result in immune tolerance against SE36 molecule. Methods: The primary trial was conducted to assess the safety and immunogenicity of the BK-SE36 in two cohorts of children aged 25-60 months (Cohort 1) and 12-24 months (Cohort 2). Immunization was at full dose (1.0 mL) administered at 0, 1, and 6 months. Blood samples were collected before each vaccination for immunological assessments and detection of Plasmodium falciparum infection by microscopy. Blood samples were further collected one month post each vaccination to evaluate immunogenicity. Results: Of seventy-two (72) subjects that have received BK-SE36 vaccination, 71 had available blood smears during vaccination days. One month post Dose 2, the geometric mean of SE36 antibodies was 263.2 (95% CI: 178.9-387.1) in uninfected individuals compared to 77.1 (95% CI: 47.3-125.7) in infected participants. The same trend was observed one-month post booster dose. Participants uninfected at the time of booster vaccination had significantly higher GMTs compared to those who were infected (424.1 (95% CI: 301.9-595.8) vs. 92.8 (95% CI: 34.9-246.6), p = 0.002. There was a 14.3 (95% CI: 9.7-21.1) and 2.4 (95% CI: 1.3-4.4) fold-change, respectively, in uninfected and infected participants between booster dose and one-month post Dose 2. The difference was statistically significant (p < 0.001). Conclusion: Concomitant infection by P. falciparum to BK-SE36 vaccine candidate administration is associated with reduced humoral responses. Trial registration: WHO ICTRP, PACTR201411000934120